2014
DOI: 10.1002/ijc.29077
|View full text |Cite
|
Sign up to set email alerts
|

Recent insights into the biology of neuroblastoma

Abstract: Neuroblastoma (NB) is an embryonal tumor of the sympathetic nervous system which accounts for 8-10% of pediatric cancers. It is characterized by a broad spectrum of clinical behaviors from spontaneous regression to fatal outcome despite aggressive therapies. Considerable progress has been made recently in the germline and somatic genetic characterization of patients and tumors. Indeed, predisposition genes that account for a significant proportion of familial and syndromic cases have been identified and genome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
85
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(89 citation statements)
references
References 90 publications
1
85
0
3
Order By: Relevance
“…Genetic alterations in neuroblastoma at diagnosis mainly concern copy number alterations, with MYCN amplification in 20% to 25% of cases, and segmental copy number alterations involving more extensive chromosome regions (10)(11)(12)(13)(14). Genome sequencing studies of neuroblastoma at diagnosis have revealed a low mutation rate involving only few recurrently altered genes mainly involved in chromatin-remodeling or neuritogenesis (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…Genetic alterations in neuroblastoma at diagnosis mainly concern copy number alterations, with MYCN amplification in 20% to 25% of cases, and segmental copy number alterations involving more extensive chromosome regions (10)(11)(12)(13)(14). Genome sequencing studies of neuroblastoma at diagnosis have revealed a low mutation rate involving only few recurrently altered genes mainly involved in chromatin-remodeling or neuritogenesis (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…These diploid tumor's cells are more likely to harbor MYCN gene amplification or other SCAs. In contrast, neartriploid DNA content is most commonly found in infant tumors that remain localized and are associated with more favorable outcome [2][3][4][5][6][7][8][9]12].…”
Section: Discussionmentioning
confidence: 99%
“…Aggressive metastatic tumors are characterized by a high number of SCAs and a low number of Numerical Changes (NCAs). On the whole, genome-wide studies have demonstrated that critical chromosomal damages occur more frequently in older patients and that SCAs accumulate in an age-dependent manner, as supported by Schleiermacher and Coco [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…[3][4][5][6]. Next-generation sequencing-based genomic profiling identified the most frequent alterations including MYCN (26.5%), ALK (17.8%), ATRX (6.5%), CDKN2A (4.8%) and RPTOR (4.8%) in 230 neuroblastoma patient samples [7].…”
Section: Introductionmentioning
confidence: 99%